Manufacturing Radially Aligned PCL Nanofibers Reinforced With Sulfated Levan and Evaluation of its Biological Activity for Healing Tympanic Membrane Perforations - Akgul, Busra; Gulcan, Cansu; Tornaci, Selay; Erginer, Merve; Toksoy Oner, Ebru; Abamor, Emrah Sefik; Acar, Serap; Allahverdiyev, Adil M. (Wiley, 2024)
AbstractThe main objective of this study is to construct radially aligned PCL nanofibers reinforced with levan polymer and investigate their in vitro biological activities thoroughly. First Halomonas levan (HL) polysaccharide is hydrolyzed (hHL) and subjected to sulfation to attain Sulfated hydrolyzed Halomonas levan (ShHL)‐based material indicating heparin mimetic properties. Then, optimization studies are carried out to produce coaxially generated radially aligned Poly(caprolactone) (PCL) ‐ShHL nanofibers via electrospinning. The obtained nanofibers are characterized with Fourier Transform Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy with Energy Dispersive X‐Ray (FESEM‐EDX) analysis, and mechanical, contact angle measurement, biodegradability, and swelling tests as well. Afterward, cytotoxicity of artificial tympanic membranes is analyzed by MTT (3‐(4,5‐Dimethylthiazol‐2‐yl) ‐2,5 Diphenyltetrazolium Bromide) test, and their impacts on cell proliferation, cellular adhesion, wound healing processes are explored. Furthermore, an additional FESEM imaging is performed to manifest the interactions between fibroblasts and nanofibers. According to analytical measurements it is detected that PCL‐ShHL nanofibers i) are smaller in fiber diameter, ii) are more biodegradable, iii) are more hydrophilic, and iv) demonstrated superior mechanical properties compared to PCL nanofibers. Moreover, it is also deciphered that PCL‐ShHL nanofibers strongly elevated cellular adhesion, proliferation, and in vitro wound healing features compared to PCL nanofibers. According to obtained results it is assumed that newly synthetized levan and PCL mediated nanofibers are very encouraging for healing tympanic membrane perforations.
Keywords: sulfated hydrolyzed halomonas levan; chronic tympanic membrane perforation; radially aligned; coaxial electrospinning; nanofiber; Research Article